1994
DOI: 10.1128/jvi.68.10.6655-6666.1994
|View full text |Cite
|
Sign up to set email alerts
|

trans activation by the full-length E2 proteins of human papillomavirus type 16 and bovine papillomavirus type 1 in vitro and in vivo: cooperation with activation domains of cellular transcription factors

Abstract: Papillomaviral E2 genes encode proteins that regulate viral transcription. While the full-length bovine papillomavirus type 1 (BPV-1) E2 peptide is a strong trans activator, the homologous full-length E2 product of human papillomavirus type 16 (HPV-16) appeared to vary in function in previous studies. Here we show that when expressed from comparable constructs, the full-length E2 products of HPV-16 and BPV-1 trans activate a simple E2-and Spl-dependent promoter up to-100-fold in human keratinocytes and other e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…The BPV1 E2 protein consistently was a strong repressor of HPV18 early gene expression, in contrast to the homologous protein (10,14,49). To test whether these functional differences might be related to DNA binding, we analyzed the binding strength of BPV1 E2 and compared it to that of the different E2 binding sites present in the LCR of HPV18.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BPV1 E2 protein consistently was a strong repressor of HPV18 early gene expression, in contrast to the homologous protein (10,14,49). To test whether these functional differences might be related to DNA binding, we analyzed the binding strength of BPV1 E2 and compared it to that of the different E2 binding sites present in the LCR of HPV18.…”
Section: Resultsmentioning
confidence: 99%
“…3 and 4 clearly demonstrated that BPV1 E2 has a higher affinity for BS-1 than HPV18 E2. Comparing the affinities of HPV16 E2 and BPV1 E2 to the equivalent HPV16 E2 binding site, the HPV16 protein also bound more weakly than the BPV1 E2 protein (49). Thus, it might be possible that the E2 proteins of a particular PV type have adopted specific DNA-binding properties, although the proteins are highly conserved in their DNA binding domains and they recognize the same consensus sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies indicated that there might be differences between the activities of the BPV-1 and HPV E2 proteins (29,59,60), but these differences might have arisen solely because the expression vectors employed for the BPV-1 and HPV E2 proteins were not equivalent or because subcloning of the E2 ORFs into these vectors introduced variable noncoding sequences which affected expression levels. More recent studies (6,61) have employed equivalently constructed expression plasmids containing the BPV-1 and HPV type 16 (HPV-16) E2 coding regions. Whereas Ushikai et al (61) came to the conclusion that these two E2 proteins are similar in their activation properties, the experiments of Bouvard et al (6) indicated that their comparative activities are dependent upon the reporter system used.…”
mentioning
confidence: 99%
“…E2 of the papillomavirus plays crucial multi-functional roles in its life cycle, including regulation of viral gene expression [Dong et al, 1994;Ushikai et al, 1994], participation in genome replication [Kasukawa et al, 1998;, and ensuring persistent infection of the host cells through faithful segregation [Lehman et al, 1997;Abroi et al, 2004]. Although the general structure of the E2 protein consists of an amino-terminal transactivation domain linked by a hinge domain to the carboxyl-terminal DNA binding domain, there are substantial variations in the amino acid sequences of E2s from different papillomavirus subtypes [Chan et al, 1995;Garcia-Vallve et al, 2005].…”
Section: Introductionmentioning
confidence: 99%